Neto, Tomaz; Prado, Henrique (Orgs). União Europeia – Visões Brasileiras. 1 ed. Curitiba: Appris Editora, 2019, 255p. ISBN: 978-85-473-3200-6 - de Araujo, Flavia Loss (Mural Internacional, 2021)
A obra discute diversos aspectos da União Europeia e de seu relacionamento com o Brasil que, apesar de longo, ainda não rompeu os limites do desconhecimento mútuo. Assim, os artigos analisam as experiências da integração europeia nas áreas do comércio, direitos humanos, educação, regulação de fronteiras e cooperação internacional, propondo a ampliação dessas agendas de pesquisa a partir de perspectivas brasileiras. Palavras-chave: União Europeia; Integração regional; Cooperação internacional ABSTRACT The work discusses several aspects of the European Union (EU) and its long relationship with Brazil, seeking to identify areas of synergy to expand the partnership between the two actors. The authors emphasize the need for more work that addresses the theme and consolidates this research agenda in Brazil, especially in a context of growing distance between Brazil and the EU. Thus, the articles analyze the experiences of European integration in the areas of trade, human rights, education, border regulation and international cooperation, proposing the discussion of these themes from Brazilian perspectives. Keywords: European Union; Regional integration; International cooperation. Recebido em: 25 jan. 2021 | Aceito em: 30 mar. 2021.